Meningkatkan Hasil Belajar pada Materi “Peran Keluarga Bagi Perkembanganku” Melalui Model PBL Bagi Peserta Didik Kelas VII SMP Negeri 6 Tempunak - Polania Polania; Alfonsus Mudi Aran; Aserie M.M. Dungus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to reminded student learning outcomes and determine the ability of the teachers to manage in learning through the problem-based learning model in PAK grade VII-C SMP Negeri 6 Tempunak. This type of research is classroom action research (PTK) which consist of two cycles. The research subject of students in grade VII-C SMP Negeri 6 Tempunak amounted to thirty-two students consisting of seventeen male students and fifteen female students. The data collection technique in this study uses observation, test and documentation. The result of study was that the average score of students in the first cycle was seventy-two percent then increased eighty-one percent in the second cycle. The improvement was seen significantly for students who needed attention and guidance from teachers and classmates. This can be seen from the fact that number of students has increase quite a bit by fourty-one percent. This means that, if the PBL learning model is implements properly and consistently, it will improve student learning outcomes.